SARS-CoV-2 Incidence Evolution in Itapúa, Paraguay, from February to August 2021 (Journal on studies and research of academic knowledge, 2022)
Approximately two years after the start of the Covid-19 pandemic, the number of confirmed cases in Paraguay by the end of August 2021 raises to 458,207 people, and the number of reported deaths to 15,653. This investigation was carried out in order to evaluate the evolution of the incidence of the SARS-CoV-2 virus in patient samples from the Molecular Biology laboratory of the Hospital Regional de Encarnación-Itapúa. The samples were taken during the months of February and August of 2021. A descriptive, prospective cross-sectional study was carried out where 22312 samples were analyzed. The identification of the virus was carried out mainly by the qRT-PCR technique Starting in May, the rapid test technique for antigen detection was introduced. The prevalence of positive cases for Covid-19 in patients residing in the department of Itapúa was 28% (6229), May being the month with the highest percentage of cases (23,24%, 1448). 55.5% of the cases (3460) represented the female group and the most affected age group was people between 21 and 40 years old was 51.2% (3191). The Ct value for the E gene had a mean of 24.75 ± 6.55. The most frequent comorbidities correspond to chronic heart disease, obesity, and diabetes. This study analyzed data from Itapúa that showed an increase in cases in the months between May and July. It was determined that there is a statistically significant relationship between suffering from some comorbidity and death caused by Covid-19.
Keywords: Covid-19; SARS-CoV-2; Itapúa